Gene and protein expression profiles of JAK-STAT signalling pathway in the developing brain of the Ts1Cje down syndrome mouse model - Lee, Han Chung; Md Yusof, Hadri Hadi; Leong, Melody Pui Yee; Zainal Abidin, Shahidee; Seth, Eryse Amira; Hewitt, Chelsee A.; Vidyadaran, Sharmili; Nordin, Norshariza; Scott, Hamish S.; Cheah, Pike See; Ling, King Hwa (Taylor & Francis, 2019)
Aims: The JAK-STAT signalling pathway is one of the key regulators of pro-gliogenesis process during brain development. Down syndrome (DS) individuals, as well as DS mouse models, exhibit an increased number of astrocytes, suggesting an imbalance of neurogenic-to-gliogenic shift attributed to dysregulated JAK-STAT signalling pathway. The gene and protein expression profiles of JAK-STAT pathway members have not been characterised in the DS models. Therefore, we aimed to profile the expression of Jak1, Jak2, Stat1, Stat3 and Stat6 at different stages of brain development in the Ts1Cje mouse model of DS.